LifeReview: Um modelo para acompanhamento de pessoas com transtorno de ansiedade - Paula, Leonardo dos Santos; Barbosa, Jorge Luis Victória (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
This article presents LifeReview, a model that aims to facilitate the therapeutic process and the interaction between patients and mental health professionals, helping them in the treatment of anxiety disorder. The model uses as a basis the records of dysfunctional thoughts, a tool widely used by cognitive-behavioral therapy, incorporating it into an application capable of collecting media data and the patient's location. Allied to this, a management panel allows the therapist to visualize and interact with the sent records, besides personalizing the patient's experience through tips and techniques for anxiety control. A prototype was developed following the model specifications and evaluated with specialists in the area through scenarios, denoting a potential treatment aid.